Small business computers made in Europe (1960s-1980s) between booking machines and the PC - Henrich-Franke, Christian 1975-; Röhr, Matthias 1983-; Nomos Verlagsgesellschaft (Historische Dimensionen Europäischer Integration, 2024)
The technical and economic history of data technologies tends to focus on the US history of mainframes and personal computers. From this perspective, genuinely European developments in data processing are often declared to be non-innovative marginal phenomena. However, long before the triumph of the PC, with its version of “mid-range computing”, the European office machine industry brought computers into offices “. This volume analyzes how office machines were developed into computers in Europe in the 1960s and successfully sold on European markets, until the PC became a universal office machine in the 1980s. From the perspective of companies, national, and European Community industrial and research policies, it shows this European path into the computer age.